Levels of Cognitive Depth and Their Relationship to Environmental Advocacy Skills Among Biology Teachers for the Preparatory Stage - Abbas Karim, Ahmed (Universitas Islam Tribakti Lirboyo Kediri, 2023)
The aim of this research is to develop a comprehensive scale for assessing the cognitive depth levels of middle school biology teachers and to construct a corresponding scale for evaluating environmental advocacy skills among teachers in the preparatory stage. The study also seeks to ascertain the cognitive depth levels of preparatory stage biology teachers and explore potential differences in these levels based on gender (male or female). Additionally, the research aims to assess the extent of environmental advocacy skills among preparatory stage biology teachers and examine any disparities in these skills based on gender. The research focuses on the relationship between the depth of knowledge levels and environmental advocacy skills among preparatory stage biology teachers. The study was conducted among biology teachers in preparatory schools under the Directorate of Education of Al-Qadisiyah for the academic year 2022-2023. The research sample comprised 150 teachers randomly selected from various schools. Two well-validated tools were utilized: the first being a measure of cognitive depth levels, and the second, a scale to assess environmental advocacy skills among preparatory stage biology teachers. The tools were applied during the second semester of the academic year 2022-2023 in preparatory schools situated in the center of Al-Qadisiyah Governorate. The obtained data underwent rigorous statistical analysis using Microsoft Excel and the Statistical Package for the Social Sciences (SPSS). The research outcomes include the successful development of a scale for measuring cognitive depth levels and another for assessing environmental advocacy skills among middle school biology teachers. The findings reveal that preparatory stage biology teachers exhibit a commendable level of cognitive depth and a high proficiency in environmental advocacy skills. Furthermore, a direct correlation was identified between cognitive depth levels and environmental advocacy skills.